Travels in imaginary landscapes : An analysis of four cultural historic guidebooks - Grete Swensen; Karoline Daugstad (Belgeo)
The market for selling experiences and products influenced by various connotations of the past is continuously increasing. Guidebooks play a role in introducing cultural history to a growing tourist market. A study of four European cultural historic guidebooks draws attention to some of the differences that appear in the way national heritage assets are presented. The analysis reveals that guidebooks are more restricted in representation form and writing genre than initially presumed. By choosing a representation form dominated by a cartographic style of writing, where factual information play a dominant role, the text in the guidebooks leaves the reader in the role of a distanced observer. It is primarily via the illustrations that the heritage assets act as a scene for contemplation, involvement or for adventure. The material is interpreted within a framework that draws attention to the interaction that takes place between the representations of the past and contemporary society.